1992
DOI: 10.1038/355846a0
|View full text |Cite
|
Sign up to set email alerts
|

Clonal expansion of p53 mutant cells is associated with brain tumour progression

Abstract: Tumour progression is a fundamental feature of the biology of cancer. Cancers do not arise de novo in their final form, but begin as small, indolent growths, which gradually acquire characteristics associated with malignancy. In the brain, for example, low-grade tumours (astrocytomas) evolve into faster growing, more dysplastic and invasive high-grade tumours (glioblastomas). To define the genetic events underlying brain tumour progression, we analysed the p53 gene in ten primary brain tumour pairs. Seven pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
277
2
10

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 600 publications
(304 citation statements)
references
References 9 publications
13
277
2
10
Order By: Relevance
“…A prediction of our functional analysis is that the p16W alleles, which appear to contain non-inactivating mutations, would confer no selective growth advantage in relation to the wild-type p16 INK4a allele (Sidransky et al, 1992). Indeed, these ®ve alleles (A73T, H98Y, V106M, R107C, P114S) were reported in malignant gliomas (Kyritsis et al, 1995(Kyritsis et al, , 1996 but each of these CDKN2A mutations was detected only in a small percentage of the tumor cells by individual colony sequencing and Southern hybridization, consistent with heterogeneous glioma cell populations (Kyritsis et al, 1996), in which the mutations do not appear to have been selected.…”
Section: Discussionmentioning
confidence: 95%
“…A prediction of our functional analysis is that the p16W alleles, which appear to contain non-inactivating mutations, would confer no selective growth advantage in relation to the wild-type p16 INK4a allele (Sidransky et al, 1992). Indeed, these ®ve alleles (A73T, H98Y, V106M, R107C, P114S) were reported in malignant gliomas (Kyritsis et al, 1995(Kyritsis et al, , 1996 but each of these CDKN2A mutations was detected only in a small percentage of the tumor cells by individual colony sequencing and Southern hybridization, consistent with heterogeneous glioma cell populations (Kyritsis et al, 1996), in which the mutations do not appear to have been selected.…”
Section: Discussionmentioning
confidence: 95%
“…Early studies suggested that p53 abnormalities contribute to the development of malignant transformation in astrocytic brain tumours (Frankel et al, 1992;Sidransky et al, 1992). Loss of heterozygosity on human chromosome 17p, 53 point mutations, and altered p53 expression were reported in astrocytomas (Scheffner et al, 1990;Werness et al, 1990;Fujimaki et al, 1991;Lowe and Ruley, 1993;Chozick et al, 1994a;Iuzzolino et al, 1994;Slebos et al, 1994;Morita et al, 1996;Sarkar et al, 2002).…”
mentioning
confidence: 99%
“…The three mtDNA mutations identified in the primary samples were suggested to be highly significant in epithelial ovarian cancer; yet were actually absent in the TSC clones -although one (A10398G) was expressed in the normal germ line profile of the patient. Thereby, although TSCs have a distinct genetic identity within the gross tumor as do a multitude of other nontransformed stem cell lineages, the overall dominant expression would be germ line (at initial stages of tumorigenesis) and mixed mutant-germ line at later stages (due to overlap of expressions of dominating clones in the tumor; Sidransky et al, 1992). This suggests that genetic profiling of entire tumors could often be a confusing exercise and possibly lead to errors in tumor classification (Alonso et al, 2005).…”
Section: Discussionmentioning
confidence: 99%